2020
DOI: 10.3390/w12030788
|View full text |Cite
|
Sign up to set email alerts
|

Using the Freshwater Health Index to Assess Hydropower Development Scenarios in the Sesan, Srepok and Sekong River Basin

Abstract: Sustainable water resource management is a wicked problem, fraught with uncertainties, an indeterminate scope, and divergent social values and interests among stakeholders. To facilitate better management of Southeast Asia’s transboundary Sesan, Sekong and Srepok (3S) River basin, we used the Freshwater Health Index (FHI) to diagnose the basin’s current and likely future level of freshwater health. We used the conditions for December 2016 as a baseline, where Ecosystem Vitality and Ecosystem Services scored 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…The results of Souter et al [13] December 2016 FHI assessment (A summary of these findings is also available from the FHI website, http://www.freshwaterhealthindex.org/basin-reports.) found that, whilst the 3S basin's water ecosystem was showing signs of stress (with an Ecosystem Vitality score of 64), it provided a suite of desired ecosystem services (with an Ecosystem Services score of 80), but the water governance system was weak (with a Governance and Stakeholders score of 43).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of Souter et al [13] December 2016 FHI assessment (A summary of these findings is also available from the FHI website, http://www.freshwaterhealthindex.org/basin-reports.) found that, whilst the 3S basin's water ecosystem was showing signs of stress (with an Ecosystem Vitality score of 64), it provided a suite of desired ecosystem services (with an Ecosystem Services score of 80), but the water governance system was weak (with a Governance and Stakeholders score of 43).…”
Section: Methodsmentioning
confidence: 99%
“…found that, whilst the 3S basin's water ecosystem was showing signs of stress (with an Ecosystem Vitality score of 64), it provided a suite of desired ecosystem services (with an Ecosystem Services score of 80), but the water governance system was weak (with a Governance and Stakeholders score of 43). The work of Souter et al [13] also assessed a range of future hydropower scenarios, which predicted that, as the number of dams increased, Ecosystem Vitality and Ecosystem Service scores will decline.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations